2021
DOI: 10.1016/j.orggeochem.2020.104160
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of sympagic-benthic coupling revealed by analyses of n-3 fatty acids, IP25 and other highly branched isoprenoids in two filter-feeding Arctic benthic molluscs: Mya truncata and Serripes groenlandicus

Abstract: Efficiency of sympagic-benthic coupling revealed by analyses of n-3 fatty acids, IP 25 and other highly branched isoprenoids in two filter-feeding Arctic benthic molluscs: Mya truncata and Serripes groenlandicus, Organic Geochemistry (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 96 publications
(130 reference statements)
2
14
0
1
Order By: Relevance
“…HBI‐III production is thus consistent with open water conditions (Belt, 2018, 2019; Köseoğlu et al., 2018; Smik, Cabedo‐Sanz, & Belt, 2016) although recently Amiraux et al. (2021) reported the occurrence of this HBI in sea ice in southwest Baffin Bay.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…HBI‐III production is thus consistent with open water conditions (Belt, 2018, 2019; Köseoğlu et al., 2018; Smik, Cabedo‐Sanz, & Belt, 2016) although recently Amiraux et al. (2021) reported the occurrence of this HBI in sea ice in southwest Baffin Bay.…”
Section: Discussionsupporting
confidence: 69%
“…Intermediate values were found in the MIZ where brassicasterol and sympagic HBIs were abundant in accordance with our present knowledge on these biomarkers. HBI-III production is thus consistent with open water conditions (Belt, 2018(Belt, , 2019Köseoğlu et al, 2018;Smik, Cabedo-Sanz, & Belt, 2016) although recently Amiraux et al (2021) reported the occurrence of this HBI in sea ice in southwest Baffin Bay.…”
Section: Phytoplankton Biomarkerssupporting
confidence: 77%
“…3.2) can also be used as the phytoplankton biomarker in lieu of HBI III (e.g., Müller et al, 2011). Although in some regions high concentrations of HBI III have also been associated with highly productive marginal ice zones (Barents Sea, Belt et al, 2019), marine fronts (North Iceland Shelf, Harning et al, 2021), and sea ice (Amiraux et al, 2019(Amiraux et al, , 2021Koch et al, 2020) that may complicate PIP 25 -derived indices, recent compilations of Arctic surface sediments show that PIP 25 -based indices broadly correlate with spring and autumn sea ice concentrations (Xiao et al, 2015;Kolling et al, 2020).…”
Section: Hbismentioning
confidence: 99%
“…The combined hexane extracts were dried over anhydrous Na 2 SO 4 , filtered and concentrated to obtain the fatty acid fraction and methylated for further detection with gas chromatography-mass spectrometry (GC-MS). GC-MS analysis of fatty acids was carried out using selected ion monitoring (SIM) mode and an Agilent 7890A series gas chromatograph (DB 5MS fused silica column; 50 m x 0.25 mm i.d., 0.25-mm film thickness) coupled to an Agilent 5975C mass spectrometric detector (Amiraux et al, 2020). Quantification of fatty acids was carried out by comparing mass spectral intensities of molecular ions to that of the internal standard and normalizing for volume/mass sampled and differences in mass spectral fragmentation efficiency (e.g., response factors of each fatty acids identified with Supelco1 37 Component FAME Mix, Supelco).…”
Section: Lipid Analysesmentioning
confidence: 99%